Analisis Peran Komisi Pemilihan Umum Dalam Mewujudkan Pelaksanaan Demokrasi Substantif Pada Pemilihan Umum: Studi Kasus Manipulasi Data Dalam Sirekap Pada Pilpres 2024 - Mega Arinda Pramessella; Najwa Adhwa Ramadhani; Revalyza Misbah; Fadillah Nur Fakih; Achmad Aidil Viqri; Ana Sabhana Azmy (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
This research analyzes the role of the General Election Commission in realizing substantive democracy in the 2024 elections, focusing on the case of data manipulation in the Vote Recapitulation Information System. The use of Sirekap, which aims to increase efficiency and transparency, has faced challenges in the form of data anomalies and vote inflation that weaken public confidence in election results. This research uses a qualitative approach with descriptive analysis through interviews and literature studies, to evaluate the effectiveness of the General Election Commission in dealing with these problems. The results of this study show that vote inflation is caused by technical errors, lack of offering training, and potential disruptions in systems security at Sirekap. The General Election Commission has conducted an evaluation through manual checks, increased training for those involved in the vote counting process, and improvements to the Sirekap system to prevent similar incidents in the future. This study recommends system improvements, strengthened security, and increased public participation to maintain the integrity of substantive democracy in Indonesia.